Photo- and thermal-crosslinked GelMA/chitosan hydrogels: A novel approach to enhanced mechanical and biological properties - A. Moradian; M. Behzadnasab; Z. Bagher; M. Pezeshki-Modaress; M. Zandi; M.Hashemi Tabatabaei (Carbohydrate Polymer Technologies and Applications)
Tissue engineering aims to regenerate damaged tissues by replicating the native extracellular matrix (ECM). Injectable hydrogels show promise for therapeutic applications due to being biocompatible, but materials based on polysaccharides often do not have the necessary mechanical strength and stability for many applications. This study proposes a solution by creating a blend of photo crosslinkable gelatin methacrylate (GelMA) and chitosan (CS), crosslinked using Irgacure 2959 and beta-glycerol phosphate (β-GP). It presents an innovative interpenetrating network (IPN) of GelMA/CS hydrogels formed through covalent and electrostatic interactions using photo and thermal crosslinking. In vitro culturing with olfactory ecto-mesenchymal stem cells (OE-MSCs) assessed cytocompatibility. The addition of CS and β-GP significantly improved mechanical properties (12.7 times at 0.01 Hz) and increased porosity by 6 %. Hydrophilicity and swelling decreased by up to 66 % in the first hour. Enzymatic degradation showed slower rates with CS and β-GP; after 48 hours, 24 % ± 1.08 of the GM80C20 (GelMA/CS blend) remained. OE-MSCs exhibited enhanced attachment and proliferation on the GelMA/CS hydrogel in comparison with pure GelMA.